Pore heterogeneity analysis and control mechanisms in Cambrian shale of the Shuijingtuo Formation, Yichang area, China - An, Zhengzhen; Zhao, Yue; Zhang, Yanfei (Frontiers in Earth Science, 2024)
This study focuses on understanding the fractal characteristics and controlling factors of micropore structures within organic-rich shale of the Cambrian Shuijingtuo Formation in the Yichang area of Hubei Province. Mineralogy, petrology, and organogeochemical characteristics were confirmed through comprehensive testing methods, including whole-rock X-ray diffraction and organic geochemical analyses. Additional experiments included low-temperature carbon dioxide adsorption, low-temperature nitrogen adsorption, and high-pressure mercury injection. Fractal dimensions of micropores, mesopores, and macropores were calculated using the V-S, FHH, and MENGER sponge models, respectively. Results indicate that the Cambrian Shuijingtuo Formation represents a typical deposit from an alkaline water body, resulting in high-calcareous shale. Fractal dimensions were as follows: micropores (D1) ranged from 2.1138 to 2.3475 (average 2.2342), mesopores (D2) ranged from 2.5327 to 2.7162 (average 2.6171), and macropores (D3) ranged from 2.7361 to 2.9316 (average 2.82905). Correlations were observed between total organic carbon (TOC) content and Ro with D1 and D2 (positive) and D3 (negative). Shale pore volume and specific surface area exhibited positive correlations with D1 and D2 but negative correlations with D3. High bio-deposited silica positively influenced micropore and mesopore development, while clay mineral compaction and dehydration transformations favored macropore development. Carbonate minerals primarily contributed to regular macropores, with complex correlations involving fractal dimensions D1, D2, and D3. The research results provide theoretical support for analyzing pore fractal characteristics of shallow old Marine shale reservoirs and the prediction and development plan of high-quality reservoirs of the Shuijingtuo Formation in the Yichang area.